Menakar Partisipasi Politik Perempuan di Kabupaten Malang (Studi di KPUD Kabupaten Malang) - Iqbal, Mahathir Muhammad (Gorontalo Journal of Government and Political Studies, 2019)
AbstractAhead of the simultaneous elections on April 17, 2019, the issue of women's political participation becomes important to address. The rule about the 30 percent quota obligation for female candidates is one of the important achievements in the course of post-reform Indonesia's democracy. These rules are contained in a number of laws, namely Law No. 31 of 2002 concerning Political Parties, Law No. 12 of 2003 concerning General Elections, Law No. 2 of 2008 concerning Political Parties and Law No. 10 of 2008 concerning General Elections of DPR-DPRD Members which also contain rules relating to the 2009 Election. In this context, this research was conducted. By using a qualitative approach, this research produces a major conclusion that women's political participation, especially in the context of Malang Regency, has a positive trend. Thus, referring to the results of a UN study which states that the minimum number of women's involvement in politics allows for a change and impacts on the quality of decisions taken in public institutions.Keywords: Democracy, Election, Political Participation, Women AbstrakMenjelang pemilu serentak pada 17 April 2019, isu partisipasi politik perempuan menjadi penting untuk diketengahkan.Aturan tentang kewajiban kuota 30 persen bagi caleg perempuan adalah salah satu capaian penting dalam perjalanan demokrasi Indonesia pascareformasi. Aturan tersebut tertuang dalam sejumlah UU, yakni UU No. 31 Tahun 2002 tentang Partai Politik, UU No. 12 Tahun 2003 tentang Pemilihan Umum, UU No. 2 Tahun 2008 tentang Partai Politik dan UU No. 10 Tahun 2008 tentang Pemilihan Umum Anggota DPR-DPRD yang di dalamnya juga memuat aturan terkait Pemilu tahun 2009. Dalam konteks itulah penelitian ini dilakukan.Dengan menggunakan pendekatan kualitatif, penelitian ini menghasilkan sebuah kesimpulan utama bahwa partisipasi politik perempuan, terutama dalam konteks Kabupaten Malang, memiliki tren positif.Dengan begitu, merujuk pada hasil penelitian PBB yang menyatakan bahwa jumlah minimum keterlibatan perempuan dalam politik memungkinkan terjadinya suatu perubahan dan membawa dampak pada kualitas keputusan yang diambil dalam lembaga publik.